2007
DOI: 10.1021/ie070016z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of a Novel Tobermorite-Based Porous Material from Municipal Incineration Bottom Ash

Abstract: A novel tobermorite-based porous material has been synthesized from municipal incineration bottom ash (MIBA), using a hydrothermal processing method under saturated steam pressure (1.0 MPa) at 453 K for 12 h. Without additional vesicants, NaOH solution that is incorporated into the starting material acts as both a reaction solvent and a vesicant. As a reaction solvent, the NaOH solution first promoted tobermorite formation to form a huge number of small pores during hydrothermal processing; then, as a vesicant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Reactor I and II were made of stainless steel with an inner volume of 5.7 mL and 42 mL respectively, and Reactor III was a Teflon-lined stainless steel reactor with an inner volume of 28 mL. The schematic drawing of these reactors can be found elsewhere [18][19][20]. The Reactor I was made of a piece of SUS-316 stainless steel tubing (9.525 mm (3/8 in.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactor I and II were made of stainless steel with an inner volume of 5.7 mL and 42 mL respectively, and Reactor III was a Teflon-lined stainless steel reactor with an inner volume of 28 mL. The schematic drawing of these reactors can be found elsewhere [18][19][20]. The Reactor I was made of a piece of SUS-316 stainless steel tubing (9.525 mm (3/8 in.)…”
Section: Methodsmentioning
confidence: 99%
“…Reactor III with a Teflon-lined inner was also used to further study the iron conversion mechanism. The details of this reactor has been described elsewhere [20]. If there is no specific explanation, all the experiments were carried out in the Reactor I.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work showed that tobermorite formation could improve the strength of hydrothermally solidified specimens [14,15]. Tobermorite, a calcium silicate hydrate mineral of ideal composition Ca 5 Si 6 H 2 O 18 Á4H 2 O, is very rare naturally but can be synthesized by hydrothermal processes [15].…”
Section: Effect Of Addition Of Quartzmentioning
confidence: 99%
“…Tobermorite, a calcium silicate hydrate mineral of ideal composition Ca 5 Si 6 H 2 O 18 Á4H 2 O, is very rare naturally but can be synthesized by hydrothermal processes [15]. According to Table 1, addition of quartz may promote tobermorite formation because of the low Si content of the raw fly ash.…”
Section: Effect Of Addition Of Quartzmentioning
confidence: 99%
“…And all kinds of them have been researched home and abroad to produce AAC, e g, burnt waste residue [7] ; Efflorescence Sand-Phosphorus SlagLime [8] ; zeolite [9,10] ; cement bypass dust and waste container glass [11] ; riverbed sediments [12] ; municipal solid waste incineration bottom ash [13][14][15] ; blast furnace slag [16,17] ; coal fly ash [5,18] ; silty siliceous crushed stone [19] . However, the literature appears to contain few researches dealing with production of AAC with carbide slag.…”
Section: Introductionmentioning
confidence: 99%